Determination of phytase-hydrolyzable phosphorus in selected animal feed ingredients by in vitro digestion method - Canceran, Nikkaela Mae S. (Philippine Journal of Science, 2024)
Feed phytase is one of the most successful biotechnological applications that led to better farm performance and effective phosphorus (P) reduction in animal excrement. Better estimation of phytase-hydrolyzable P (PHP) in feeds can further improve the estimation of animal rations for higher productivity. PHP in yellow corn, feed wheat, wheat pollard, rice bran, soybean meal, copra meal, and monodicalcium phosphate (MDCP) was determined by in vitro digestion. To determine if PHP values of feed ingredients are additive, three formulated diets were also subjected to the same method. The procedure consisted of phytase, pepsin, and pancreatin digestion periods – each of which simulated the different sections of poultry’s gastrointestinal tract. After these three incubations, the P contents in the dialysate and residual fluids – with and without enzyme – were analyzed. Results showed that yellow corn contained the highest PHP value with 52.54% of its total soluble P – followed by soybean meal, rice bran, copra meal, and feed wheat with 52.32, 39.86, 26.77, and 21.9%, respectively. Wheat pollard and MDCP had –58.47 and –2.63%, respectively. On the other hand, formulated diets 1, 2, and 3 contained actual PHPs of 32.3, 14.02, and 38.68% – as well as calculated values of 33.22, 29.13, and 40.1%, respectively. Statistical analyses showed no significant difference between the actual and calculated values. Therefore, PHP is additive when used in diet formulation. Lastly, comparing the P in the dialysate from the experiment and the available P present in the seven feed samples based on literature indicated that the experimental values were lower than those of the literature data for all samples. This discrepancy can be attributed to the type of samples analyzed; the experimental data were obtained upon in vitro assay of individual feeds, whereas the literature values were based on an as-fed basis, which may contain other components normally fed to animals.